TACKLING CLIMATE CHANGE IN INDIA - Chansarkar, Madhuri (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Climate change happens when the average weather conditions of a place change over a period of years. Basically, it occurs due to excessive use of fossil fuels, which burn and release greenhouse gases which in turn trap the Sun’s heat and cause our planet’s temperature to rise. Climate change can lead to extreme weather events which threaten lives and livelihoods. Countries understood that climate change could be managed only by concerted efforts and this made them arrive at a landmark international treaty called The Paris Climate Agreement; wherein it was pledged to try to limit global warming to 1.5°C. India, being a developing nation faced a big dilemma, whether to give preference to environment or to prioritize development. Keeping in view the delicate balance required, the governments in India took initiatives of two types – mitigation and adaptation and put these in place through different plans and policies, energy sector interventions, industrial sector schemes, increasing green cover and financial tools. The UN Environment Program’s Emission Gap Report of 2024 , mentioned India as the only major country to be on track to achieve its targets set out in the Paris climate agreement.